Violence Against Women - Tulipat, Prescilla (Review of Women's Studies; Vol 25 No 1-2 (2015): Review of Women's Studies Volume XXV, Numbers 1-2 (January-December 2015), 2018)
Strategic Objectives: D1. Take integrated measures to prevent and eliminate violence against women D2. Study the causes and consequences of VAW and the effectiveness of preventive measures D3. Eliminate trafficking in women and assist victims of violence due to prostitution and trafficking